Are English skills really necessary for Indonesian IT specialists?. Issue 5 (October 2022) - Dewi, Rahmatika
This study investigates the potential importance of the English skills element in the context of the Indonesian IT specialist workforce. Given the apparent incongruity of Indonesian IT specialists' lack of English skills and the current rapid growth in the IT sector and the number of digital start-ups in Indonesia, a question emerges: 'Are English skills really necessary?' Drawing on semi-structured interviews with Indonesian IT specialists, companies that hire IT specialists, and a higher education institution, as well as teaching document analysis, this study explores the perceptions of IT specialists and employers in relation to the importance of English skills and investigates the supply-side role to discover whether satisfactory English courses are provided. It finds that English is not the most important skill, but that it is necessary as a supporting skill. The paper proposes a combination of English skill elements with other skill sets as meaningful to assist in creating technologies, learning new and updated technologies, and developing career trajectories in the global IT sector, especially in the current gig economy. This skill reformation concept is relevant for IT specialists' future career navigation and, as a reference, especially for the Indonesian government to design policies for a digital economy.